Television Commercial Wearout: An Information Processing View - Calder, Bobby J.; Sternthal, Brian (Journal of Marketing Research, 1980)
Repetition of a pattern of television commercials caused wearout in viewers’ evaluation of the commercials and the products being advertised. As predicted by an information processing view, wearout was not forestalled by strategies designed to enhance attention.